PENGARUH LATIHAN SEGMENTASI TERHADAP PENINGKATAN KOORDINASI MOTORIK ANAK USIA DINI DALAM OLAHRAGA RENANG GAYA BEBAS DI CLUB SWIMFUN KUNINGAN - Nurfadilah, Ade Nova; Nanang Mulyana; Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Motor coordination is a fundamental aspect of early childhood development that supports the acquisition of various movement skills, including freestyle swimming. Young children often experience difficulties in coordinating arm movements, leg kicks, breathing techniques, and body positioning simultaneously, resulting in less effective swimming performance. This study aimed to determine the effect of segmented practice on improving motor coordination in freestyle swimming among early childhood participants at Swimfun Club Kuningan. The research employed a quantitative approach using a quasi-experimental method with a one-group pretest–posttest design. The sample consisted of 10 children aged 4–6 years who actively participated in swimming training at Swimfun Club Kuningan. The segmented practice program was implemented over 18 training sessions. Data were collected using the Test of Gross Motor Development-2 (TGMD-2) and analyzed through descriptive statistics, the Shapiro–Wilk normality test, Levene's homogeneity test, and a paired sample t-test using SPSS version 26. The findings revealed that the mean motor coordination score increased from 81.40 in the pretest to 89.70 in the posttest. The hypothesis test produced a significance value of 0.000 (p < 0.05) with a t-value of 6.851, indicating that segmented practice had a statistically significant effect on improving motor coordination. Therefore, segmented practice can be recommended as an effective instructional method for enhancing motor coordination in freestyle swimming among early childhood learners.